Late Pleistocene-Holocene coastal adaptation in central Mediterranean: Snapshots from Grotta d'Oriente (NW Sicily). (10th November 2018) - Colonese, A.C.; Lo Vetro, D.; Landini, W.; Di Giuseppe, Z.; Hausmann, N.; Demarchi, B.; d'Angelo, C.; Leng, M.J.; Incarbona, A.; Whitwood, A.C.; Martini, F.
Abstract: Marine faunal remains from Grotta d'Oriente (Favignana Island, NW Sicily) offer invaluable snapshots of human-coastal environment interaction in the central Mediterranean from the Late Pleistocene to the Middle Holocene. The long-term shellfish and fish records reflect human exploitation of coastal environments undergoing considerable reorganizations during the postglacial sea level rise and the progressive isolation of Favignana from mainland Sicily. We detected an intensification of marine resource exploitation between ∼9.6 ka and ∼7.8 ka BP, which corresponds with the isolation of Favignana Island and, later on, with the introduction of early agro-pastoral economy in this region. We suggest that a higher investment in marine resource exploitation by late foragers and early farmers in NW Sicily was also supported by an increase in marine productivity in the south Tyrrhenian Sea in the Middle Holocene.